Essence of the service category in forensic merchandising - Petrova, Iryna; Dontsova, Olga (Archives of Criminology and Forensic Sciences, 2020)
The article states that market of services, as a field of economic activity, plays the role of a leading sector of the national economy is not without certain problems, among which was the possibility of evaluating the service within the forensic merchandising. It is noted that researchers of the concept of service paid attention to its direct definition, description of the characteristics inherent in services and identify differences between the concepts: Goods, service, work. It is established the essence of the concept of service remains debatable and insufficiently researched regarding its application in forensic merchandising. In view of this, various structural elements of the concept of service were systematized into a single holistic definition by studying scientific approaches, terminological analysis and refining the definitions of this concept from different sources. It is established that uncertainty of services is that they are processes, not material objects and do not fall under the traditional definition of goods; identified a number of properties that distinguish services from tangible goods, and identified specific features of intangible services. It is emphasized that researching on category essence of service in forensic merchandising, one cannot ignore the interpretation of this term by legislators and scholars. Analysis of the service definition in regulations has established that the generalizing concept of service for these acts is a service as an action that has a certain beneficial effect, i.e. has benefits for consumer. Scientists argue that the service usually is an intangible product, process, and ownership of it for its sale to the consumer does not arise; ownership may arise as a result of the provision of the service. The essential service characteristic is defined by scientists as economic value, which makes it an object of commercial activity, a subject of trade and an object of purchase and sale; it turns it into an economic good. It is established that service concept is most often associated with the action or activity of the service provider aimed at meeting the needs of the consumer and is realized at the time of its provision.